Application of self-assembled hemispherical microlasers as gas sensors - Ta, Van Duong (2013)
Dye-doped hemispherical resonators are self-assembled on a distributed Bragg reflector based on hydrophobic effect. The size of hemispheres can be well-controlled with diameters ranging from 5 to 150 um. Upon optical pumping, whispering gallery mode laser emission with transverse magnetic polarization is observed from the hemispheres. Application of the microlasers as refractive index gas sensors has been demonstrated by detecting the spectrum shift of the lasing mode, and the sensitivity higher than 130 nm/RIU is achieved. Our approach provides an effective technique to obtain high quality microlasers and opens an opportunity to employ the cost effective microlasers as high sensitive sensors.